The price of civilization : reawakening American virtue and prosperity - Sachs, Jeffrey (New York : Random House, 2011)
Offers a diagnosis of the country's economic ills and argues that Americans can restore the virtues of fairness, honesty, and foresight as the foundations of national prosperity.
The great crash -- Diagnosing America's economic crisis -- Prosperity lost -- The free-market fallacy -- The retreat from public purpose -- The divided nation -- The new globalization -- The rigged game -- The distracted society -- The path to prosperity -- The mindful society -- Prosperity regained -- Paying for civilization -- The seven habits of highly effective government -- The millennial renewal.
Includes bibliographical references (p. [277]-307) and index.
Keywords: Environmental responsibility -- United States; Social responsibility of business -- United States; United States -- Economic conditions -- 2009-; United States -- Economic policy -- 2009-; United States -- Politics and government -- 21st century